2019
DOI: 10.1200/po.18.00338
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Inherited Risk in Unselected Newly Diagnosed Patients With Endometrial Cancer

Abstract: PURPOSE Mutations in DNA mismatch repair genes and PTEN, diagnostic of Lynch and Cowden syndromes, respectively, represent the only established inherited predisposition genes in endometrial cancer to date. The prevalence of other cancer predisposition genes remains unclear. We determined the prevalence of pathogenic germline variants in unselected patients with endometrial cancer scheduled for surgical consultation. PATIENTS AND METHODS Patients prospectively consented (April 2016 to May 2017) to an institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…12 Mutations in cancer susceptibility genes (CSGs) other than those associated with LS are thought to play a smaller role in EC risk. 13 Although multigene panel testing (MGPT) studies performed for women with EC have identified PVs in other CSGs, [14][15][16] the true burden of PVs in other CSGs remains unknown. The modest number of cases investigated (381 in the study by Ring et al, 14 156 in Cadoo et al, 15 and 98 in Samadder et al 16 ), coupled with the fact that the cohorts overrepresent women with nonendometrioid, high-grade, and higher-stage tumors, limits our understanding of how frequent PVs in other CSGs are in the general EC population.…”
Section: Introductionmentioning
confidence: 99%
“…12 Mutations in cancer susceptibility genes (CSGs) other than those associated with LS are thought to play a smaller role in EC risk. 13 Although multigene panel testing (MGPT) studies performed for women with EC have identified PVs in other CSGs, [14][15][16] the true burden of PVs in other CSGs remains unknown. The modest number of cases investigated (381 in the study by Ring et al, 14 156 in Cadoo et al, 15 and 98 in Samadder et al 16 ), coupled with the fact that the cohorts overrepresent women with nonendometrioid, high-grade, and higher-stage tumors, limits our understanding of how frequent PVs in other CSGs are in the general EC population.…”
Section: Introductionmentioning
confidence: 99%
“…Although associations with specific genomic characteristics are unknown, CS was more likely to be present in those with EC and age at diagnosis <50, macrocephaly, and concurrent renal cell carcinoma [7]. This study and others highlight the low yield of germline testing in unselected EC patients [10], however certain clinical features such as those seen in this patient, including younger age of diagnosis, macrocephaly, and concurrent cancers, may warrant germline assessment.…”
Section: Characteristics Of Cs and Germline Pten Mutationsmentioning
confidence: 59%
“…Although many environmental risk factors for EC have been identified, an inherited predisposition is thought to be present in about 5% of women with this disease [9,10]. The most common inherited syndrome in EC is Lynch syndrome, which is associated with MMRdeficient (MMRd)/microsatellite instability-high (MSI-H) tumors, as well as colon cancers and other cancers exhibiting an MMRd/MSI-H phenotype [11].…”
Section: Inherited Syndromes Predisposing To Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic ancestry analysis shows 90% TCGA-LCs were inferred as genetic European ancestry 83 . However, it is possible that a small portion of European ancestry TCGA-patients has AJ origin, given that 7% of ovarian cancer 84 and 24% of endometrial cancer 85 are of AJ heritage. It is of note that in our dataset, none of the variant allele carriers of the 25 candidates were found to have African-ancestry.…”
Section: Discussionmentioning
confidence: 99%